Protein conversion efficiency in French dairy small ruminant systems - Jost J.; Fança B.; Bluet B.; Morin E.; Bienne F.; Rouillé B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Dairy production is facing social issues due to competition in the use of resources (feeds, water and land). The French livestock Institute (Idele) has characterized feed conversion efficiency for the dairy small ruminants in France. DIAPASON database from a reference farms’ network (INOSYS-Réseaux d’élevage) has been used to determine the efficiency of a large number of dairy systems in France between 2012 and 2016. Systems studied in this reference network are on average net producers of proteins: 52% for dairy sheep and almost 50% for dairy goats. Diet composition is of critical importance. Cereals are directly in competition with human nutrition while grass as pasture or silage are not, giving a positive impact on efficiency. This is why we show that grass-based dairy systems, specifically those with pasture, are very efficient to turn proteins from grass into high-quality proteins for human nutrition. A high variability within and between systems and species is shown and gives the opportunity to propose technical ways to improve this new approach on farm.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)